2022
DOI: 10.1111/ced.15380
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a pilot forensic dermatology curriculum in the USA

Abstract: Physician participation in asylum medicine through forensic medical evaluations increases the likelihood that asylum seekers are granted legal status. Based on a review of existing literature and input from content experts, we designed and implemented a forensic dermatology curriculum for dermatology residents at University of California, San Francisco. Our pilot curriculum led to improvements in learners' attitudes regarding physician participation in asylum medicine and their confidence in describing skin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…4 Preassessment and postassessment analyses found that residents demonstrated improved attitudes and knowledge regarding the importance of asylum medicine. 4…”
Section: Forensic Dermatologymentioning
confidence: 99%
See 2 more Smart Citations
“…4 Preassessment and postassessment analyses found that residents demonstrated improved attitudes and knowledge regarding the importance of asylum medicine. 4…”
Section: Forensic Dermatologymentioning
confidence: 99%
“…Formal curricula in forensic dermatology and asylum medicine provide an opportunity to introduce trainees to the field, as does providing structured opportunities to directly support asylum applications. The University of California, San Francisco, implemented a pilot curriculum in forensic dermatology for dermatology residents . Preassessment and postassessment analyses found that residents demonstrated improved attitudes and knowledge regarding the importance of asylum medicine …”
Section: Approaches To Providing Dermatologic Care For Displaced Personsmentioning
confidence: 99%
See 1 more Smart Citation